Positron Emission Tomography Imaging of Vascular Endothelial Growth Factor Receptor Expression with (61)Cu-Labeled Lysine-Tagged VEGF(121) - Zhang, Yin (2012)
Overexpression of vascular endothelial growth factor (VEGF) and VEGF receptors (VEGFRs) indicates poor prognosis for cancer patients in a variety of clinical studies. Our goal is to develop a tracer for positron emission tomography (PET) imaging of VEGFR expression using recombinant human VEGF(121) with three lysine residues fused to the N-terminus (denoted as K(3)-VEGF(121)), which can facilitate radiolabeling without affecting its VEGFR binding affinity. K(3)-VEGF(121) was conjugated with 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) and labeled with (61)Cu (t(1/2): 3.3 h; 62% β(+)). The IC(50) value of NOTA-K(3)-VEGF(121) for VEGFR-2 was comparable to K(3)-VEGF(121) (1.50 and 0.65 nM, respectively) based on cell binding assay. (61)Cu labeling was achieved with good yield (55 ± 10 %) and specific activity (4.2 GBq/mg). Serial PET imaging showed that the 4T1 tumor uptake of (61)Cu-NOTA-K(3)-VEGF(121) was 3.4 ± 0.5, 4.9 ± 1.0, 5.2 ± 1.0, and 4.8 ± 0.8 %ID/g (n = 4) at 0.5, 2, 4, and 8 h post-injection respectively, which was consistent with biodistribution data measured by gamma counting. Blocking experiments and ex vivo histology confirmed VEGFR specificity of (61)Cu-NOTA-K(3)-VEGF(121). Extrapolated human dosimetry calculation showed that liver was the organ with the highest radiation dose. The use of (61)Cu as the radiolabel is desirable for small proteins like K(3)-VEGF(121), which has much higher β(+) branching ratio than the commonly used (64)Cu (62% vs. 17%) thereby offering stronger signal intensity and lower tracer dose for PET imaging.